2012
DOI: 10.1016/j.rvsc.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and protective efficacy of the recombinant Pasteurella lipoprotein E and outer membrane protein H from Pasteurella multocida A:3 in mice

Abstract: Pasteurella multocida serotype A:3 is a Gram-negative bacterial pathogen, one of the causative agents of shipping fever of cattle. In this study, outer membrane protein H (ompH) and Pasteurella lipoprotein E (plpE) genes were cloned and plpEC-ompH fusion was constructed and expressed in Escherichia coli. Recombinant PlpE, OmpH and PlpEC-OmpH fusion proteins were purified and formulated with oil-based and oil-based CpG ODN adjuvants. Antibody responses in mice vaccinated with recombinant PlpE and PlpEC-OmpH pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However, a plpE knockout mutant strain retained full virulence (416). Conjugated vaccines comprised of multiple antigens, such as OmpH plus PlpE peptides, have also shown promise (445,565).…”
Section: Vaccinationmentioning
confidence: 99%
“…However, a plpE knockout mutant strain retained full virulence (416). Conjugated vaccines comprised of multiple antigens, such as OmpH plus PlpE peptides, have also shown promise (445,565).…”
Section: Vaccinationmentioning
confidence: 99%
“…Both of LppC and HAPS_0926 are outer membrane lipoproteins. Lipoproteins are widely distributed in Gram-negative bacteria, which are involved in diverse mechanisms of physiology/pathogenesis and are considered potential target antigens for vaccine development against many infectious diseases [3031]. Our previous study demonstrated that the VacJ lipoprotein was a good vaccine candidate against Glässer's disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Purification of the recombinant proteins was performed according to Okay et al [15]. The recombinant E. coli BL21(DE3) cells with pET-28a(+) vectors carrying erp, hspR, lppX, mmaA4, and ompA genes were grown in Luria Broth (Merck, Germany) containing kanamycin (30 μg/ml) at 37°C until logarithmic growth phase.…”
Section: Purification Of the Recombinant Erp Hspr Lppx Mmaa4 And mentioning
confidence: 99%
“…The secondary antibody, alkaline phosphatase-conjugated anti-mouse IgG (Sigma, Germany), was used at a dilution of 1:10,000. The AP Conjugate Substrate Kit (Bio-Rad, CA, USA) was used for visualization of the bands [15].…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation